2020
DOI: 10.21203/rs.3.rs-60899/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LDL-C/HDL-C is associated with ischaemic stroke in patients with non-valvular atrial fibrillation: a case-control study

Abstract: Background: This study explored the relationships between the low-/high-density lipoprotein cholesterol ratio (LDL-C/HDL-C) and other clinical indicators and ischaemic stroke (IS) in patients with non-valvular atrial fibrillation (NVAF) in Xinjiang. The findings could provide a theoretical and therapeutic basis for NVAF patients.Methods: NVAF patients who were admitted to 10 medical centres across Xinjiang were divided into stroke (798 patients) and control (2671 patients) groups according to the occurrence of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Four blood lipids—TC, TG, LDL‐C, and HDL‐C—are important indicators used to reveal changes in blood lipids (Chen et al, 2021). Earlier studies showed that HDL‐C levels negatively correlate with carotid atherosclerosis progression (Hedayatnia et al, 2020; Teis et al, 2021), while higher LDL‐C levels and lower HDL‐C levels might correlate with cardiovascular diseases (CVDs) such as stroke (Zhang, Wei, et al, 2020). This LDL‐C/HDL‐C ratio was proved to be more valuable than any single lipid component—especially LDL‐C—to predict CVDs risk (Hedayatnia et al, 2020; Zhang, Wei, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Four blood lipids—TC, TG, LDL‐C, and HDL‐C—are important indicators used to reveal changes in blood lipids (Chen et al, 2021). Earlier studies showed that HDL‐C levels negatively correlate with carotid atherosclerosis progression (Hedayatnia et al, 2020; Teis et al, 2021), while higher LDL‐C levels and lower HDL‐C levels might correlate with cardiovascular diseases (CVDs) such as stroke (Zhang, Wei, et al, 2020). This LDL‐C/HDL‐C ratio was proved to be more valuable than any single lipid component—especially LDL‐C—to predict CVDs risk (Hedayatnia et al, 2020; Zhang, Wei, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals over 75, the incidence rate of AF was negatively correlated with LDL-C/HDL-C ratio (RR = 0.75, 95% CI 0.61-0.94) [29]. A Chinese case-control study of 3469 patients revealed that compared with the lowest LDL-C/HDL-C quartile, the occurrence risk of ischemic stroke (IS) was 16.23-fold that of highest quartile in patients with non-valvular AF (NVAF) [56]. As with the Multi-Ethnic Study of Atherosclerosis (MESA) and the Framing-ham Heart Study, compared with HDL-C <40 mg/dL, high levels of HDL-C for ≥60 mg/dL were related to lower risk of AF (adjusted HR 0.64, 95% CI 0.48-0.87), while higher TG levels was correlated with higher AF risk in those with levels ≥200 mg/dL versus <150 mg/dL (adjusted HR 1.60, 95% CI 1.25-2.05) [34].…”
Section: Epidemiologymentioning
confidence: 99%